1994
DOI: 10.1007/bf01310798
|View full text |Cite
|
Sign up to set email alerts
|

Expression kinetics and subcellular localization of HIV-1 regulatory proteins Nef, Tat and Rev in acutely and chronically infected lymphoid cell lines

Abstract: Information concerning the expression kinetics and subcellular localization of HIV regulatory proteins is of importance in understanding the viral pathogenesis and may be relevant for drug and vaccine development, as well. We have used combined immunocytochemistry and in situ hybridization to study firstly, the order of expression of regulatory HIV-1 proteins Nef, Rev and Tat in relation to non-spliced and spliced mRNA expression and secondly, the subcellular localization of these proteins in acutely and chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 54 publications
(54 reference statements)
2
63
1
Order By: Relevance
“…Antagonizing the function of Nef pharmacologically could be a means of increasing the efficiency of protective CTL responses. Because the Nef protein is expressed early in the viral life cycle (45), it is unclear whether Nef-specific CTL could be more effective than other CTL, by recognizing infected cells earlier and before the onset of Nef-mediated effects. Another strategy could be to produce or enhance MHC-I C-restricted CTL responses.…”
Section: Discussionmentioning
confidence: 99%
“…Antagonizing the function of Nef pharmacologically could be a means of increasing the efficiency of protective CTL responses. Because the Nef protein is expressed early in the viral life cycle (45), it is unclear whether Nef-specific CTL could be more effective than other CTL, by recognizing infected cells earlier and before the onset of Nef-mediated effects. Another strategy could be to produce or enhance MHC-I C-restricted CTL responses.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, in the replicative cycle, Rev and Tat are expressed earlier than the structural proteins. This may allow specific CTL to kill infected cells well before release of progeny virus (Ranki et al, 1994 ;Riviere et al, 1994). Although both considerations would also hold true for Nef, specific CTL responses to this protein were observed in most progressors.…”
Section: Hla-a1 (X[st]xxxxxxy)mentioning
confidence: 99%
“…Recent reports on virus escape from HIV-1-specific CTL responses clearly indicate that CTL exert pressure on virus replication in vivo, but that the overall CTL efficacy may be dependent on the (lack of) conservation in the epitope sequences (Borrow et al, 1997 ;Goulder et al, 1997). In addition, it has been suggested that CTL responses against early expressed epitopes may be more efficacious than those against late expressed epitopes (Ranki et al, 1994 ;Riviere et al, 1994). Qualitative and quantitative analyses of specific CTL responses, before the immune status has deteriorated, may identify the requirements for a CTL response to be protective.…”
mentioning
confidence: 99%
“…HIV-1 encodes an additional protein, Vpu, but lacks the open reading frame for Vpx. After viral entry, reverse transcription, and integration of the viral genome, the first genes expressed by HIV/ SIV are completely spliced mRNAs that encode for the nonstructural Tat, Rev, and Nef proteins (12)(13)(14). Only when Rev reaches a sufficient level are the incompletely spliced Env mRNA and the genomic RNA encoding for Env and Gag-Pol, respectively, transported to the cytoplasm for translation.…”
Section: H Uman Immunodeficiency Virus Type 1/siv Infection Is Associmentioning
confidence: 99%